A pilot study on parents' knowledge, attitude, and practices on soil-transmitted helminth infection and its prevalence among volunteer respondents from Arsenio H. Lacson Elementary School, Manila - Julian Felipe T. Canzon, Monacita D. Cucal, Christian Sofia A. De Padua, Princess Dianne S. Laurado, Bojoe M. Lauresta 4 0 16; 5
u
Undergraduate Thesis: (Bachelor of Science in Biology) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2